Possibility of nutritional enrichment of whipped dairy products - Greta Krešić; Vesna Lelas; Zoran Herceg (Mljekarstvo)
Nutritional value in addition to diverse physico-chemical and functional properties make whey proteins highly suitable for food purpose. One of important functional demand of whey proteins is their capability to induce and stabilize aerated food products.The aim of this work was to obtain whey protein isolate and β-lactoglobulin with improved foaming properties, what will in addition to its high nutritional value, make them more acceptable for use in whipped dairy products. For these purpose, whey protein isolate and β-lactoglobulin were treated with high hydrostatic pressure of 400, 500 and 600 MPa, for holding period of 10 minutes. Solubility changes were expressed as nitrogen solubility. Turbidity measurements of diluted protein solutions were used to obtain information about protein aggregation in addition to scanning electron microscopicpictures. Assessment of foaming properties has been based on the foam volume and foam stability. All analysis were carried out on whey protein isolate and β-lactoglobulin before and after high pressure treatment. The results obtained showed pressure-induced structural changes together with partial denaturation in both samples proportional to the intensity of applied pressure. The observed effects of pressure treatments on foaming properties clearly indicate that the extent of pressure-induced changes in the physicochemical properties of whey protein isolate and β-lactoglobulin positively affected foamability and foam stability, respectively.